ROLA CZYNNIKÓW AFEKTYWNYCH NA PRZYKŁADZIE STREFY KOMFORTU NA ZDALNYCH ZAJĘCIACH JĘZYKOWYCH - Jankowiak, Agnieszka (Neofilolog, 2021)
Affective factors are one of the two types of individual factors that influence success in the process of foreign language learning. They consist of personality traits, as well as positive and negative emotions. This emotional dichotomy is also reflected in the popular concept of comfort zone. The aim of this paper is to define the comfort zone in the context of distance learning language classes and to check if and how it is possible to implement this model in research in the field of glottodidactics. The results of empirical research on the perception and experience of the comfort zone during synchronous distance learning classes by philology students are presented and analyzed in order to draw conclusions on the impact of positive and negative emotions on the process and effects of the language distance learning.